Peran pendidikan kearsipan dalam menghidupkan arsip dan kehidupan sosial - Bramantya, Arif Rahman (Perpustakaan Universitas Gadjah Mada, 2020)
Introduction. The establishment of archival science study programs at the undergraduate (including archival applied) level leads to efforts to develop archival education and fulfillment of the needs of professional archivists. This paper discusses the importance of established and strong archival education by implementing more effective competency standards. Data Collection Method. The method used in this research was literature study with qualitative approach. Data Analysis. The data was analyzed by using a descriptive-analytic approach. Results and Discussion. The establishment of the archiavl study programs will have great impacts on the quality of the graduates. The establishment also affected the scientific development of archival science, with the fact that the number of archival science study programs is limited. The non-standard curriculum by each study program also needs to be further professionally discussed. Conclusion. Competency standards in professional archivist development must ensure the clear objectives and tailored competency to support the archival science. Finally, archival education is to form humans’ characteristics to solve social problems in society, particularly the field of archival education.